Two-stage bargaining solutions - Paola Manzini; Marco Mariotti (Queen Mary University of London, Department of Economics, 2006)
We introduce and characterize a new class of bargaining solutions: those which can be obtained by sequentially applying two binary relations to eliminate alternatives. As a by-product we obtain as a particular case a partial characterization result by Zhou (Econometrica, 1997) of an extension of the Nash axioms and solution to domains including non-convex problems, as well as a complete characterizations of solutions that satisfy Pareto optimality, Covariance with positive affine transformations, and Independence of irrelevant alternatives.
Keywords: C72; D44; 330; Bargaining; Non-convex problems; Nash bargaining solution